Lixiviación del Cs-137 en matrices cementadas - Mallaupoma, Mario (2008)
The leaching rate of Cs-137 from the chemical treatment process in cement matrix has been studied. The solidification matrix was a standard Portland cement mixed with 5–10% of bentonite clay. The cement specimens were prepared from construction cement which is basically a standard Portland cement. The mixtures were cast into 50 mm diameter cylindrical molds with a height of 50 mm, which were then sealed and cured for 28 days prior to the leaching experiments. The leaching rates from the cement matrix for 137Cs : 2 E–05 (cm/d), after 155 days were measured. The results presented in this paper are part of the results obtained in a 2 years concrete testing work which will be used for conditioning of sludge from the chemical precipitation of decontamination waste.